Financial Performance Segmentation Changes on Indonesian Insurance Companies - Tonggo, Andohar; Rachman Zarkasih, Aditya; Heikal, Jerry (Economic Reviews Journal, 2024)
Company acquisition is one of the strategies for developing and maintaining the company's survival, especially if unforeseen situations occur that are detrimental to a company, for example in the insurance industry during the Covid-19 pandemic. The purpose of this study is to determine changes in the performance of financial ratios of insurance companies from 2021 to 2022 which can be used as consideration for making acquisitions. The method used is quantitative using k-mean clustering in SPSS software and ranking is made based on DER, ROE, NPM and RBC analysis. Based on the data above, it can be seen that there are companies that have changed from 2021 to 2022. There are 7 companies that have experienced an increase in status, 5 companies that have experienced a decline and 5 companies that have not experienced a change. The most recommended company for acquisition is Lippo General Insurance Tbk and the recommended company for acquisition is Panin Financial Tbk and dan Panininvest Tbk.